Achieving overall water splitting using titanium dioxide-based photocatalysts of different phases1. Issue 8 (29th August 2015) - Li, Rengui; Weng, Yuxiang; Zhou, Xin; Wang, Xiuli; Mi, Yang; Chong, Ruifeng; Han, Hongxian; Li, Can
<x xml:space="preserve">Abstract</x> Photocatalytic overall water splitting on TiO2-based photocatalysts is determined by both thermodynamics and kinetics simultaneously.